Development of VR Apps with Kodular & Sketchfab SIMUJI Hajj Pillars Simulation in Elementary School - Ani Nur Aeni; Arif Hidayat; Salwa Naofalia; Kania Indah Pratiwi; Desnawita Dwi Anggita (TA`DIBUNA, 2025)
This research aims to develop a virtual reality application based on kodular and sketchfab called SIMUJI, as a medium in learning Islamic Religious Education (PAI) grade 5 SD on the material of the pillars of Hajj. The importance of this topic is in the need for students to improve their understanding of the Hajj pilgrimage, which is often only taught theoretically, resulting in a gap between knowledge and real experience. The method used in this research is Design & Development (D&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The findings show that the SIMUJI application can increase students' interest and understanding of the material on the pillars of Hajj, as well as provide an interactive learning experience. The conclusion of this study is that the use of VR technology in learning about the pillars of Hajj can overcome shortcomings in traditional learning methods, as well as provide an innovative alternative to improve the quality of Islamic religious education in elementary schools. This application is expected to be a reference for the development of other learning media in the future.